The role of YouTube platform as a learning resource in online learning effectiveness - Diva Fikri Harry Adnan; Norma Istiqomah (Universitas Pendidikan Indonesia, 2022)
The COVID-19 pandemic has resulted in teachers using media more creatively in the learning process, one of which is using video-based media via YouTube. This study aims to find out the role and implementation as well as the obstacles that arise in using YouTube as a learning resource in supporting the effectiveness of online learning based on the perceptions or views of students. The research uses quantitative methods with primary data sources and data collection using surveys or questionnaires involving active students as respondents. The study results show that most respondents agree that using YouTube is a practical learning resource or online learning media. However, there are still some obstacles encountered in practice. So, the YouTube platform had a good impact on the effectiveness of online learning during the COVID-19 pandemic and increased opportunities for using YouTube as a learning media. Abstrak Pandemi COVID-19 mengakibatkan guru harus memanfaatkan media dengan lebih kreatif pada proses pembelajaran, salah satunya adalah penggunaan media berbasis video melalui YouTube. Penelitian ini bertujuan untuk mengetahui bagaimana peranan dan penerapan serta hambatan yang muncul dalam menggunakan YouTube sebagai sumber belajar dalam menunjang efektivitas pembelajaran daring berdasarkan persepsi atau pandangan para peserta didik. Penelitian menggunakan metode kuantitatif dengan sumber data primer dan pengumpulan datanya menggunakan kegiatan survei atau kuesioner dengan melibatkan peserta didik aktif sebagai responden. Hasil penelitian menunjukkan sebagian besar responden setuju bahwa penggunaan YouTube efektif untuk digunakan sebagai sumber belajar atau media pembelajaran daring, walaupun masih ada beberapa hambatan yang dialami dalam praktiknya. Sehingga, dapat disimpulkan bahwa platform YouTube memberikan dampak baik terhadap efektivitas pembelajaran daring pada masa pandemi COVID-19 dan meningkatkan peluang pemanfaatan YouTube sebagai media pembelajaran. Kata Kunci: COVID-19; pembelajaran daring; sumber belajar; sumber kurikulum; YouTube